2018
DOI: 10.1017/s1742058x18000103
|View full text |Cite
|
Sign up to set email alerts
|

Race, Crime, and the Changing Fortunes of Urban Neighborhoods, 1999–2013

Abstract: For over a century, scholars have traced higher levels of serious crime in minority compared to White neighborhoods to stark socioeconomic inequality. Yet, this research is largely cross-sectional and does not assess how ethnoracial differences in crime patterns evolve over time in response to shifting structural conditions. The new century witnessed substantial changes to the circumstances that undergird the ethnoracial divide in neighborhood crime as well as a national crime decline. How are the changing dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 51 publications
(98 reference statements)
2
19
0
Order By: Relevance
“…Other researchers have added that it is important to consider not only offending but also violent victimization if we are to understand how race and ethnic inequality shape crime in the United States (Sampson & Lauritsen, ; Xie, ). Somewhat consistent with the findings of Krivo and colleagues (), Janet Lauritsen and I have found that, even at the national level, Black and Latino males experienced increases in victimization rates during economic recessions up through the early 2000s, which was not the case for White males (Lauritsen & Heimer, ). One great advantage to studying race and class inequities in crime by examining victimization is that we can use the National Crime Victimization Survey (NCVS) to create estimates of exposure to violence among minority groups and can assess the role of poverty in explaining group differences.…”
Section: Developments In Research On Inequalities and Crimesupporting
confidence: 80%
See 2 more Smart Citations
“…Other researchers have added that it is important to consider not only offending but also violent victimization if we are to understand how race and ethnic inequality shape crime in the United States (Sampson & Lauritsen, ; Xie, ). Somewhat consistent with the findings of Krivo and colleagues (), Janet Lauritsen and I have found that, even at the national level, Black and Latino males experienced increases in victimization rates during economic recessions up through the early 2000s, which was not the case for White males (Lauritsen & Heimer, ). One great advantage to studying race and class inequities in crime by examining victimization is that we can use the National Crime Victimization Survey (NCVS) to create estimates of exposure to violence among minority groups and can assess the role of poverty in explaining group differences.…”
Section: Developments In Research On Inequalities and Crimesupporting
confidence: 80%
“…Moreover, when the next cycles of economic crises hit, they are predicted to be most devastating for the already destitute (Edin & Shaefer, ) or the hyperdisadvantaged (Peterson & Krivo, ). We need more work along the lines of Peterson and Krivo's (, Krivo et al., ) recent research, in which they pinpoint the most highly disadvantaged groups that will be most vulnerable to crime, violence, and victimization when the next economic downslide occurs. Criminologists would do well to continue researching how cross‐cutting inequalities create particularly acute disadvantage and exposure to crime and violence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Shaw and McKay's original formulation, other scholars have theorized about the relationship between immigration and neighborhood transformation (Branic and Hipp ; Kirk and Laub ; Krivo et al. ; McDonald ; MacDonald et al. ).…”
Section: Theorizing Neighborhood Changementioning
confidence: 99%
“…The number of studies confirmed that poverty leads to crime rates [1][2][3][4][5][6][7][8] while on the reverse side, the causal mechanism has been observed and concluded that higher crime rates lead to poverty incidence across countries. [9][10][11][12][13] These studies are largely discussed with different determinants of poverty and crime rates in different economic settings. These studies are on the same finding that poverty and crime interlinked with each other that affect socioeconomic and environmental factors, which influenced country's sustained growth in the long-run.…”
Section: Introductionmentioning
confidence: 99%